Oxford reading tree : level 2 : more songbirds phonics : the doll in the bin - Donaldson, Julia ([S.l.] : Oxford University Press, 2012)
Written by award-winning author Julia Donaldson, Songbirds Phonics are highly decodable, beautifully illustrated real stories. In The Doll in the Bin, Beth's doll needs rescuing! The Level 2 More Songbirds phonics books revise all phonics previously covered in Songbirds Levels 1+ and 2, and focus on matching a sound to one letter or more: for example, 'll' as in 'will' and 'th' as in 'that.' The invaluable inside cover notes enable parents/carers and teaching assistants to support children's word recognition and comprehension. Also available: * More Songbirds Level 2 Pack of 6 * More Songbirds Level 2 Class Pack of 36 * Level 1+-2 eSongbirds Phonics CD-ROM, featuring e-versions of much-loved Songbirds stories for your interactive whiteboard, with audio activities and animations for consolidation and reinforcement.